POLA RESISTENSI Staphylococcus KOAGULASE NEGATIF TERHADAP ANTIBIOTIK YANG DIISOLASI DARI KULTUR DARAH NEONATUS TERSANGKA SEPSIS DI INSTALASI PERAWATAN NEONATUS RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE 01 JANUARI-31 DESEMBER 2014 - Karina "; Dewi Anggraini; Nazardi Oyong (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTNeonatal sepsis is one of several most common causes of neonates mortality in developing countries. Neonatal sepsis is defined as a disseminated disease with positive blood culture during the first month of life. The aim of this study was to find how many cultures presented positive and negative results and also to detect the most common bacterial causes of neonatal sepsis and determination of their sensitivity to antibiotics. This research design using a descriptive study with retrospective approach. The sampling technique is performed by total sapling method adn the amount of sample is 568 blood cultures which 196 reported as positive (34,51%) and 372 reported as negative (65,49%). The most common isolated bacteria were coagulase negative Staphylococcus (29,08%), Burkholderia cepacia (12,76%), Acinetobacter baumanii (9,18%), Klebsiella pneumoniae (8,16%), Escherichia coli (4,08%) and, Enterobacter aerogenes (4,98%). Neonatal sepsis caused by infection of coagulase negative Staphylococcus can be treated by vancomycin, linezolid and tigecycline.Keywords : neonatal sepsis, bacterial pattern, antimicrobial susceptibility, sensitivity, antibiotics.